In the house of Muhammad Ali : a family album, 1805-1952 - Hassan, Hassan, 1924-2000 (Cairo, Egypt : The American University in Cairo Press, 2000)
"This memoir of a junior member of the former royal family constitutes a unique chronicle of life before 1952 among the members of Egypt's ruling class. It provides insights into the lives not only of the rulers themselves, from Muhammad Ali to King Fuad and King Farouk, but also of royal wives, cousins, aunts, uncles, and associated personalities. In the House of Muhammad Ali is a personal memoir from the inside; it is thus an important document for future scholars."--Jacket
1. Muhammad Ali 1769-1849 -- 2. Shubra and San Remo -- 3. Marg -- 4. Palaces and houses -- 5. Turkey and England -- 6. Cairo.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Muḥammad ʻAlī family; Muḥammad ʻAlī Bāshā, -- Governor of Egypt, -- 1769-1849 -- Family; Hassan, Hassan, -- 1924-2000.; Muḥammad ʻAlī (Famille); Hassan, Hassan, -- 1924-2000; Muḥammad ʻAlī Bāshā, -- Governor of Egypt, -- 1769-1849; Muḥammad ʻAlī family; Méhémet-Ali, -- (1769-1849); Egypt -- Genealogy; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; BIOGRAPHY & AUTOBIOGRAPHY -- Royalty; Families; Egypt; Égypte -- Histoire; Genealogy